Current state of aromatics production using yeast: achievements and challenges - Liu, Quanli; Liu, Yi; Chen, Yun; Nielsen, Jens (Current opinion in biotechnology, 2020)
[Display omitted] •Cell factories-mediated bioproduction represents a renewable and sustainable alternative to aromatics production.•De novo biosynthesis of various aromatics has been achieved with yeast.•Non-optimized cellular metabolism limits the industrial application of aromatics cell factories.•Evolution of metabolic engineering principles holds promise for creating commercially viable aromatics bioproduction. Aromatics find a range of applications in the chemical, food, cosmetic and pharmaceutical industries. While production of aromatics on the current market heavily relies on petroleum-derived chemical processes or direct extraction from plants, there is an increasing demand for establishing new renewable and sustainable sources of aromatics. To this end, microbial cell factories-mediated bioproduction using abundant feedstocks comprises a highly promising alternative to aromatics production. In this review, we provide the recent development of de novo biosynthesis of aromatics derived from the shikimate pathway in yeasts, including the model Saccharomyces cerevisiae as well as other non-conventional species. Moreover, we discuss how evolved metabolic engineering tools and strategies contribute to the construction and optimization of aromatics cell factories.